Promoting individual and organization-oriented sustainable behaviors among employees in tourism and hospitality - Chua, Bee-Lia; Chi, Xiaoting; Wichupankul, Surarak; Lee, Jin-Soo; Meng, Bo; Han, Heesup (Elsevier, 2024)
Despite the relevance of pro-environmental activity among employees in the workplace, the mechanism for encouraging green practices at work has received little attention in the tourism and hospitality literature. This study supports the application of self-determination and social exchange theories to improve understanding of the interplay between individual and organizational elements in developing eco-friendly behavior among employees at home and in the workplace. A quantitative survey of 374 tourism and hospitality personnel in the United States was undertaken. Individual-oriented elements (value-belief-practice norms) and organizational factors (organizational support for the environment and psychological ownership) were found to have a favorable influence on employees’ eco-friendly activities at work. It emphasized the significance of adopting environmentally friendly habits at home to influence environmentally conscious behavior in the workplace. Additionally, psychological ownership plays a pivotal role in mediating the connection between organizational support and environmentally friendly practices at work.